Kekuatan Hukum Meterai dalam Perjanjian Perdata: Analisis Keabsahan dan Kekuatan Pembuktian Menurut KUH Perdata - Khoirul Anam; Alfina Saharani (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal force of stamp duty in civil agreements by analyzing its relationship with contractual validity and evidentiary strength under the Indonesian Civil Code. Using a normative juridical approach, the research focuses on statutory regulations, legal doctrines, and scholarly works related to contract law, evidentiary law, and stamp duty regulation. The findings demonstrate that stamp duty does not constitute a legal requirement for the validity of a civil agreement, as contractual validity is determined solely by the fulfillment of subjective and objective requirements stipulated in Article 1320 of the Civil Code. Stamp duty functions primarily as an administrative and fiscal instrument connected to the use of written documents as evidence in civil proceedings. Both conventional stamps and electronic stamps serve an equivalent role in supporting documentary evidence without altering the substantive legal relationship created by the parties’ consent. The study highlights the importance of distinguishing between contractual validity and evidentiary requirements to avoid legal misconceptions in contractual practices. Clarifying the legal position of stamp duty contributes to greater legal certainty and supports the adaptation of civil law to digital transactions while preserving fundamental principles of contract law.